Characteristics of infants or children presenting to outpatient bronchopulmonary dysplasia clinics in the United States. Issue 6 (13th March 2021) - Collaco, Joseph M.; Agarwal, Amit; Austin, Eric D.; Hayden, Lystra P.; Lai, Khanh; Levin, Jonathan; Manimtim, Winston M.; Moore, Paul E.; Sheils, Catherine A.; Tracy, Michael C.; Alexiou, Stamatia; Baker, Christopher D.; et al.
Abstract: Introduction: Bronchopulmonary dysplasia (BPD) is a common respiratory sequelae of preterm birth, for which longitudinal outpatient data are limited. Our objective was to describe a geographically diverse outpatient cohort of former preterm infants followed in BPD‐disease specific clinics. Methods: Seven BPD specialty clinics contributed data using standardized instruments to this retrospective cohort study. Inclusion criteria included preterm birth (<37 weeks) and respiratory symptoms or needs requiring outpatient follow‐up. Results: A total of 413 preterm infants and children were recruited (mean age: 2.4 ± 2.7 years) with a mean gestational age of 27.0 ± 2.8 weeks and a mean birthweight of 951 ± 429 grams of whom 63.7% had severe BPD. Total, 51.1% of subjects were nonwhite. Severe BPD was not associated with greater utilization of acute care/therapies compared to non‐severe counterparts. Of children with severe BPD, differences in percentage of those on any home respiratory support ( p = .001), home positive pressure ventilation ( p = .003), diuretics ( p < .001), inhaled corticosteroids ( p < .001), and pulmonary vasodilators ( p < .001) were found between centers, however no differences in acute care use were observed. Discussion: This examination of a multicenter collaborative registry of children born prematurely with respiratory disease demonstrates a diversity of management strategies among geographically distinct tertiary care BPD centers in the United States. This study reveals that the majority of children followed in these clinics were nonwhite and that neither variation in management nor severity of BPD at 36 weeks influenced outpatient acute care utilization. These findings suggest that post‐neonatal intensive care unit factors and follow‐up may modify respiratory outcomes in BPD, possibly independently of severity.